Reversible electrical percolation in a stretchable and self-healable silver-gradient nanocomposite bilayer - Park, Jinhong; Seong, Duhwan; Park, Yong Jun; Park, Sang Hyeok; Jung, Hyunjin; Kim, Yewon; Baac, Hyoung Won; Shin, Mikyung; Lee, Seunghyun; Lee, Minbaek; Son, Donghee (Nature communications, 2022)
The reversibly stable formation and rupture processes of electrical percolative pathways in organic and inorganic insulating materials are essential prerequisites for operating non-volatile resistive memory devices. However, such resistive switching has not yet been reported for dynamically cross-linked polymers capable of intrinsic stretchability and self-healing. This is attributable to the uncontrollable interplay between the conducting filler and the polymer. Herein, we present the development of the self-healing, stretchable, and reconfigurable resistive random-access memory. The device was fabricated via the self-assembly of a silver-gradient nanocomposite bilayer which is capable of easily forming the metal-insulator-metal structure. To realize stable resistive switching in dynamic molecular networks, our device features the following properties: i) self-reconstruction of nanoscale conducting fillers in dynamic hydrogen bonding for self-healing and reconfiguration and ii) stronger interaction among the conducting fillers than with polymers for the formation of robust percolation paths. Based on these unique features, we successfully demonstrated stable data storage of cardiac signals, damage-reliable memory triggering system using a triboelectric energy-harvesting device, and touch sensing via pressure-induced resistive switching. Smart healthcare devices, which interacts with the human body by recording, analyzing and processing physiological signals, need soft and biocompatible electronics. Here, Son et al. report a self-healable and stretchable resistive switching random-access memory made of a Ag-gradient nanocomposite.